Maintaining Life Satisfaction in Adolescence: Affective Mediators of the Influence of Perceived Emotional Intelligence on Overall Life Satisfaction Judgments in a Two-Year Longitudinal Study - Sánchez-Álvarez, Nicolás; Extremera, Natalio; Fernández-Berrocal, Pablo (Frontiers in Psychology, 2015)
Much attention has been paid to the psychological processes underlying the improvement in mood states and human well-being, particularly during adolescence. Theoretical and empirical research suggests that emotional skills may play a role in enhancing perceived well-being; however the mechanisms involved in during adolescence are unclear. The purpose of this study was to extend understanding by investigating the potential mediators of the relationship between emotional intelligence and life satisfaction in a two-year study. Participants were 269 high school students (145 girls and 124 boys) who completed the self-report Perceived Emotional Intelligence Scale (PEIS), the Satisfaction with Life Scale (SWLS), and the Positive Affect and Negative Affect Scale (PANAS) three times at one-year intervals. The three-step longitudinal design corroborated earlier research indicating that positive and negative affect mediate the relationships between emotional intelligence and life satisfaction. Students with high PEI tended to have more positive experiences and fewer negative experiences, which contributed to their greater life satisfaction. No sex differences were found in the multi-group analyses, suggesting that the causal relationships are similar in both sexes. These findings extend our understanding of the complex network of relationships involving perceived emotional intelligence and life satisfaction in adolescence. Implications and limitations of the findings are discussed.